2017
DOI: 10.1515/prilozi-2017-0028
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Ultrasound Guided Central Venous Catheterization Compared to Blind Catheterization

Abstract: introduction:Central venous catheterization is performed by the landmark method and ultrasound guided method. The purpose of the study was to compare the success, average number of attempts, average time to return of blood, and complication rate between the two methods. Material and Methods:This was a prospective study done in the Intensive Care Unit of the Acibadem Sistina Clinical Hospital, in Skopje. There were 400 patients in need of central venous catheter and they were prospectively randomized in two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 33 publications
2
28
0
1
Order By: Relevance
“…The incidence of carotid puncture in the US group is significantly lower than the LM group, confirming the results of previous studies (Denys et al, 1993;Karakitsos et al, 2006). Sazdov et al (2017) reported a 14.5% complication rate in the landmark guided techniques versus a 4% rate when using ultrasound (Sazdov et al, 2017). Other studies have reported similar significantly lower complication rates in the ultrasound guided method (Froehlich et al, 2009;Lamperti et al, 2012;Turker et al, 2009).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The incidence of carotid puncture in the US group is significantly lower than the LM group, confirming the results of previous studies (Denys et al, 1993;Karakitsos et al, 2006). Sazdov et al (2017) reported a 14.5% complication rate in the landmark guided techniques versus a 4% rate when using ultrasound (Sazdov et al, 2017). Other studies have reported similar significantly lower complication rates in the ultrasound guided method (Froehlich et al, 2009;Lamperti et al, 2012;Turker et al, 2009).…”
Section: Resultssupporting
confidence: 85%
“…These results are consistent with the findings of Turker et al study (Turker et al, 2009). However, other studies have demonstrated an increased rate of successful catheterizations in the US group when compared with the LM group (Karakitsos et al, 2006;Sazdov et al, 2017;Serafimidis et al, 2009). This contradictory between our results and otherscould be attributed to the fact that at JUH usually trained senior residents insert central venous catheters, reducing failure rates.…”
Section: Resultssupporting
confidence: 85%
“…Zu dieser Zeit waren die zur Verfügung stehenden Ultraschallgeräte weit weniger geeignet als heute. Jüngere Studien zeigen klar, dass die Anwendung der ultraschallgesteuerten Punktion die Komplikationsraten reduzieren und die Erfolgsquoten erhöhen kann [7,8,14,21,25]. Diese Studie soll kein Plädoyer für die landmarkengestützte Technik sein.…”
Section: Interventionsgruppenunclassified
“…The incidence of complications based on experience and body surface markings can increase to 14.5%. 2 Pneumothorax and a misplaced catheter are the most common insertion complications. Other rare complications include carotid artery pseudoaneurysm, 3 thyroid neck stem injury, and puncture injury to the phrenic nerve 4 causing chylothorax 5 and pericardial tamponade.…”
Section: Discussionmentioning
confidence: 99%